2006
DOI: 10.1177/0267323105064047
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Sensationalism in Dutch Current Affairs Programmes 1992–2001

Abstract: Both news critics and scholars often contend that increasing competition in the news market urges journalists to sensationalize their stories. Starting from this hypothesis, this article investigates changes in the level of sensationalism in three Dutch current affairs programmes that merged in 1996 as part of a strategy to fight increasing competition. A content analysis of these programmes in 1992 and 2001 shows a partial trend towards greater use of sensationalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
6
0
3
Order By: Relevance
“…Other techniques observed were the use of zoom-in (in 41.9% of the newscasts), zoom-out (38.7%) and close-up (35.5%); all were more frequent than in the Vettehen et al (2006) study.…”
Section: Television Trendsmentioning
confidence: 75%
See 1 more Smart Citation
“…Other techniques observed were the use of zoom-in (in 41.9% of the newscasts), zoom-out (38.7%) and close-up (35.5%); all were more frequent than in the Vettehen et al (2006) study.…”
Section: Television Trendsmentioning
confidence: 75%
“…Taking sensationalist features into account (Vettehen et al, 2006), we identified the presence of several sensationalist items used to present stem cell research in a favorable light. Various technical resources such as close-ups and zoom-in (when the camera moves closer) were used with scientists who favored stem cell research.…”
Section: Television Trendsmentioning
confidence: 99%
“…Es posible identificar varias tendencias en la literatura internacional para caracterizar la presencia del modelo infoentretenimiento en el producto informativo: la preponderancia de emociones y del enfoque humano en el discurso (Van Zoonen y Holz-Bacha, 2000), la creciente personalización de la cobertura (Van Aelst, Sheafer y Stanyer, 2012), el protagonismo de la vida privada (Stanyer, 2012; Casero-Ripollés, Ortells-Badenes y Rosique-Cedillo, 2014), así como el uso de un tono sensacionalista y morboso a la hora de abordar la actualidad política (Vettehen, Nuijten y Beentjes, 2006;Hanusch, 2013).…”
Section: Introductionunclassified
“…Entre os programas noticiosos/informativos e os de entretenimento, encontram-se os de infotainment, que procuram ao mesmo tempo informar e entreter e têm ocupado um espaço crescente na grade televisiva. Alguns autores alertam, no entanto, que pode haver certa tensão entre o entretenimento e a narração dos fatos (VETTEHEN, NUIJTEN, BEENTJES, 2006;SURETTE, OTTO, 2002;SIQUEIRA, 1998). Se a ênfase é colocada no entretenimento, pode ser, em alguma medida, negligenciada a preocupação com a apresentação dos conteúdos -pelo menos na forma de apresentação da informação tal como se espera dos programas noticiosos - (GÖRKE, RUHRMANN, 2003).…”
unclassified